Unveiling coronary inflammation by perivascular fat angio-CT: a propensity-matched score analysis. (25th November 2020) - Lopes Da Cunha, G.J; Rocha, B.M.L; Freitas, P.N; Lopes, P.M.D; Santos, A.C; Guerreiro, S; Abecasis, J; Aguiar, C.M.T; Andrade, M.J; Saraiva, C; Mendes, M; Ferreira, A
Abstract: Background: Inflammation plays a pivotal role in the atherogenic process and recently has been the target of successful clinical trials. A new CT angiography method allows the identification of inflammatory pericoronary fat, which is associated with cardiovascular events. We aimed to determine whether patients with obstructive coronary artery disease (CAD) have a higher pericoronary inflammatory milieu when compared to those without CAD. Methods: From a prospective CT angiography registry of patients with suspected obstructive CAD, those with a luminal stenosis >70% confirmed by invasive coronary angiography were screened (previous coronary artery bypass grafting was an exclusion criteria). Subsequently, we applied a 1:1 propensity score (PS) without replacement protocol to match obstructive CAD patients with those without CAD (non-CAD), using age, gender, BMI, hypertension, dyslipidemia, diabetes and smoking status as covariates. Similar to previous reports, pericoronary fat characterization by CT angiography was performed by analyzing the fat attenuation index (FAI) at the −30 to −190 HU range. Inflammatory fat was defined by a FAI >−70 HU. The proximal 50mm of the right coronary artery (RCA) was used to perform fat quantification and characterization. The perivascular fat was defined as the adipose tissue within a radial distance from the outer vessel wall equal to the diameter of the vessel. Results: A matched cohort of 48 patients was identified (mean age 63 years; 77% males) – 24 obstructive CAD and 24 non-CAD patients. Mean FAI was numerically higher in obstructive CAD compared to the non-CAD cohort (−74±7 vs −78±7; p=0.083). Although not statistically significant, those with obstructive CAD had an increased proportion of inflammatory fat (51±10 vs 46±10%; p=0.107). After adjustment for body surface area (BSA), differences in the inflammatory fat proportion became apparent between obstructive CAD and non-CAD patients (28±6 vs 24±5%/m 2 ; p=0.024). Furthermore, we observed a significant correlation between the inflammatory fat proportion (both absolute value and BSA adjusted) and the total number of RCA plaques (r=0.458; p=0.003; and r=0.451; p=0.003, respectively). Finally, there was 1 additional plaque observed in the RCA for each increase in 10% of proportion of inflammatory fat (p=0.018). Conclusions: Perivascular coronary inflammation, as measured by FAI, seems significantly heightened in patients with obstructive CAD compared to a matched cohort of non-CAD patients. Further studies are needed to ascertain the mechanisms and possible implications of this association. Funding Acknowledgement: Type of funding source: None